PENGARUH SERVICE FAIRNESS, EMPATHY DAN PHYSICAL ENVIRONMENT TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY - Evelina Larisa Sidharta; Keni Keni (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2015)
: Tujuan penelitian: (a) untuk mengetahui pengaruh service fairness, empathy dan physical environment terhadap customer loyalty; (b) untuk mengetahui pengaruh service fairness, empathy dan physical environment terhadap customer satisfaction; (c) untuk mengetahui pengaruh customer satisfaction dan customer loyalty; (d) untuk mengetahui pengaruh customer satisfaction dalam memediasi service fairness, empathy dan physical environment terhadap customer loyalty. Populasi dalam penelitian ini adalah seluruh pelanggan salah satu kedai kopi di Jakarta. Sampel diperoleh dari pelanggan salah satu kedai kopi di Jakarta Barat. Metode pengambilan sampel dalam penelitian ini adalah teknik purposive dengan jumlah 250 responden.Teknik analisis data menggunakan analisis regresi dan analisis jalur. Hasil penelitian: (a) service fairness, empathy dan physical environment mempunyai pengaruh yang positif terhadap customer loyalty; (b) service fairness, empathy dan physical environment mempunyai pengaruh yang positif terhadap customer satisfaction; (c) customer satisfaction mempunyai pengaruh positif terhadap customer loyalty; (d) customer satisfaction dapat memediasi pengaruh antara service fairness, empathy dan physical environment terhadap customer loyalty.The purposes of this study are: First, to explore the effect among service fairness, empathy and physical environment on customer loyalty. Second, to explore the effect among service fairness, empathy and physical environment on satisfaction. Third, to explore the effect of customer satisfaction on customer loyalty. Fourth, to find out if customer satisfaction is able to mediate service fairness, empathy and physical environment toward customer loyalty.The population of this research are all customers from one of the coffee shopsin Jakarta.The samples are collected from one of coffee shops customers in West Jakarta. The method of data collection is purposive sampling with250 respondents. The technique of data analysis used in this study was regression analysis and mediating test to examine the hypotheses. The results are: (a) the relationship between service fairness, empathy and physical environment have a significant and positive effect toward customer loyalty; (b) the relationship between service fairness, empathy and physical environment have a significant and positive effect toward customer satisfaction; (c) customer satisfaction has a positive effect on customer loyalty; (d) customer satisfaction will mediate the effect between service fairness, empathy and physical environment on customer loyalty